EFFECTS OF CAPITAL MARKET DEVELOPMENT AND ECONOMIC GROWTH IN NIGERIA FROM 1981 – 2016 - Augustine Okon Jacob; Okon Joseph Umoh (UIR Press, 2019)
This research work examined the relationship between capital market development and economic growth in Nigeria. Time series data were collected from both secondary sources and econometric analysis of Ordinary Least Square (OLS).the data covered 1981 – 2016. The research sought to appraise the relationship of variables, such as market Capitalization (MCAP), Number of deals (ND), all share value index (ASI) and Inflation (INF) on economic growth of Nigeria. The result revealed has a positive correlation and conform to prior expectation and significantly influenced economic growth. Inflation revealed negative correlation and conformed to a priori expectation but was insignificant on the economic growth, which makes it not determinant in economic growth in Nigeria. Based on the findings of this research, conclusion was drawn and appropriate recommendations were made for the stakeholders in the capital market such as creation of awareness by government and organized private sector on the relevance and inherent benefit of investing in the capital market so as to boost the number of deals in the stock market operators